Simulasi Implementasi Load Balancing pada Jaringan Internet dengan Metode Per Connection Classifier (PCC) dan Server dengan Metode IP Hash Menggunakan GNS3 - Tanujaya, Matthew; Dewi, Christine (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
The internet connection should typically function without any issues at all times. However, there are instances where the link does not function properly because to impediments or other issues.. The GNS3 Network Simulator tool is used in this study to carry out the simulation. The goal of this strategy is to determine whether it can sustain the internet network's quality and traffic levels while distributing the load throughout the network channel. Correct server path management will also be accomplished using the IP Hash technique. Using the PCC load balancing method, the traffic load is obtained more smoothly without data accumulation. Because the other network functions as an internet provider, internet access will still be accessible even if one of these networks dies. While using IP hash, the test results obtained an average throughput with the small data request category of 16.69 KB/s. with the medium data request category of 54.31KB/s and 1200 KB/s for the large data request category.